Evidence of Fine‐Scale Genetic Structure in Tiger Sharks (Galeocerdo cuvier) Highlights the Importance of Stratified Sampling Regimes - Jessica J. Fish; Christine Dudgeon; Adam Barnett; Paul A. Butcher; Bonnie J. Holmes; Charlie Huveneers; Lauren Meyer; Laurent Vigliola; Craig D. H. Sherman; Adam D. Miller (Evolutionary Applications, 2025)
ABSTRACT Understanding the biological connections between populations is essential to wildlife management and conservation. Genetic studies play a central role in characterizing these connections, but typically require stratified sampling regimes to assess the spatial extent and strength of gene flow, and the relative influences of sex and ontogeny on patterns of connectivity. Yet, this can be challenging in some study systems, particularly in large marine species such as sharks, where genetic studies often rely on opportunistic and/or sampling conducted over large spatial scales. We demonstrate the importance of stratified sampling to identify previously undetected genetic structure in tiger sharks (Galeocerdo cuvier) off eastern Australia, where panmixia has been previously reported. We performed population genomic analyses on 414 tiger sharks, representing males and females and both juvenile‐subadult and adult‐life stages, and 21 locations spanning approximately 3000 km of eastern Australia and the Indo‐Pacific region. Similar to previous studies, we demonstrate a lack of overall genetic structure across the sampling area; however, our analysis shows evidence of spatial autocorrelation and local genetic structuring in juvenile‐subadult female tiger sharks. These results point to potential influences of sex and ontogeny on patterns of population genetic structure and connectivity in Australian tiger sharks. We discuss these findings in the context of essential habitats supporting tiger shark populations and risks of overstating the strength of biological connections among shark populations in the absence of appropriate sampling regimes.